Three-Tiered Fertilizer Application with a Spreading Funnel of a Subsoil Tiller - F. M. Mamatov; Z. L. Batirov; M. S. Khalilov; J. B. Kholiyarov (Сельскохозяйственные машины и технологии, 2019)
The authors have shown that current methods of soil fertilizing for growing cotton crops in Uzbekistan do not ensure the full supply of nutrients to the root system of plants. Providing the required amount of fertilizers is distributed in tiers in the zone of root development, the ratio of their use and cotton yield will increase. (Research purpose) To determine the design parameters of a spreading funnel of a subsoil tiller for three-tiered fertilizer application. (Materials and methods) The paper provides a design of the developed spreading funnel for three-tier fertilizer application. A subsoil tiller is equipped with a spreading funnel, which consists of a cylindrical and inclined funnel-shaped part, a conductive channel and a lower distributor. Installed in the conductive channel are two branch pipes with reflective plates that cut through the supplied fertilizers and direct them to the corresponding soil horizon. (Results and discussion) The authors have studied the movement of mineral fertilizer granules along the conductive channel; experimentally analyzed the effect of the length of the protruding part of reflective plates of the nozzle and the inclination angle of the funnel spreading pipeline on the distribution of fertilizers and the unevenness of fertilizer supply to the upper, middle and lower tiers. They have also determined the parameters of an intake funnel of the vertical pipeline, branch pipes and movable plates of the upper and middle tiers, and a fertilizer spreader of the lower tier. (Conclusions) The authors have proved that the qualitative distribution of mineral fertilizers at predetermined application depths of the upper and middle tiers is ensured at a length of their nozzles of 260 and 240 millimeters and the protruding part of the reflective plates of the fertilizer channel of 26-30 millimeters and 33-37 millimeters, respectively. At the same time, 40-45 percent of fertilizers is distributed in the lower, i.e. the third tier. The authors have chosen optimal parameters of the lower spreading funnel: a groove inclination angle in the longitudinal-vertical plane of 17-19 degrees; a groove inclination angle in the transverse vertical plane of 29 degrees; a rear edge height of the groove in the middle part of 2.5 millimeters, and at the end – 0.5 millimeters.